2023
DOI: 10.3389/fphys.2023.1246746
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for ECG Arrhythmia detection and classification: an overview of progress for period 2017–2023

Yaqoob Ansari,
Omar Mourad,
Khalid Qaraqe
et al.

Abstract: Cardiovascular diseases are a leading cause of mortality globally. Electrocardiography (ECG) still represents the benchmark approach for identifying cardiac irregularities. Automatic detection of abnormalities from the ECG can aid in the early detection, diagnosis, and prevention of cardiovascular diseases. Deep Learning (DL) architectures have been successfully employed for arrhythmia detection and classification and offered superior performance to traditional shallow Machine Learning (ML) approaches. This su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 105 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…The recent review work [25] reported that the recent capable deep-learning-based works perform 71~100% in sensitivity, 90.12~99.57% in specificity, and 96~99.53% in accuracy. It suggests that the proposed method performs better than or is comparable to the state of the art.…”
Section: Improvement Of Vf Detection With Orthogonality Features Thro...mentioning
confidence: 99%
See 1 more Smart Citation
“…The recent review work [25] reported that the recent capable deep-learning-based works perform 71~100% in sensitivity, 90.12~99.57% in specificity, and 96~99.53% in accuracy. It suggests that the proposed method performs better than or is comparable to the state of the art.…”
Section: Improvement Of Vf Detection With Orthogonality Features Thro...mentioning
confidence: 99%
“…More recently, advanced machine-learning and deep-learning models in ECG analysis have been actively researched [24,25]. The use of deep learning might address the laborintensive issue of the handcrafted feature-extraction-based ECG analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Ribeiro et al [ 34 ] later used a residual network architecture, an architecture first developed by He et al [ 35 ] in the context of image classification, for the reliable diagnosis of 12-lead ECG signals. For a detailed review of deep learning applications in arrhythmia classification, we refer to the systematic reviews conducted by Xiao et al [ 36 ] and Ansari et al [ 37 ].…”
Section: Related Workmentioning
confidence: 99%
“…Deep Learning (DL) is a branch of ML which has emerged as a powerful approach in the field of ECG and has earned significant attention due to its ability to extract complex features and model intricate relationships automatically, allowing for more nuanced and accurate assessments of cardiac health [8]. DL systems offer the potential for continuous, real-time monitoring and increased precision in interpreting ECG signals, thereby improving the likelihood of detecting intermittent arrhythmias.…”
Section: Introductionmentioning
confidence: 99%